CircRNA-regulated immune responses of asian honey bee workers to microsporidian infection - Zhu, Zhiwei; Wang, Jie; Fan, Xiaoxue; Long, Qi; Chen, Huazhi; Ye, Yaping; Zhang, Kaiyao; Ren, Zhongmin; Zhang, Yang; Niu, Qingsheng; Chen, Dafu; Guo, Rui (Frontiers in Genetics, 2022)
Nosema ceranae is a widespread fungal parasite for honey bees, causing bee nosemosis. Based on deep sequencing and bioinformatics, identification of circular RNAsin host and circRNA-regulated immune response of host to microsporidian invasion were conducted in this current work, followed by molecular verification of back-splicing sites and expression trends of circRNAs. Here, 10185 and 7405 circRNAs were identified in the midguts of workers at 7 d (AcT1) and 10 d (AcT2) with microsporidian. PCR amplification result verified the back-splicing sites within three specific circRNAs expressed in microsporidian-inoculated midgut. In combination with transcriptome data from corresponding un-inoculated midguts (AcCK1 and AcCK2), 2266 circRNAs were found to be shared by the aforementioned four groups, whereas the numbers of specific ones were 2618, 1917, 5691, and 3723 respectively. Further, 83 (52) differentially expressed circRNAs (DEcircRNAs) were identified in AcCK1 vs AcT1 (AcCK2 vs AcT2) comparison group. Source genes of DEcircRNAs in host at 7 dpi were involved in two cellular immune-related pathways such as endocytosis and ubiquitin mediated proteolysis. Additionally, competing endogenous RNA (ceRNA) network analysis showed that 23 (13) DEcircRNAs in AcCK1 vs AcT1 (AcCK2 vs AcT2) comparison group could target 18 (14) miRNAs and further link to 1111 (1093) mRNAs. These target mRNAs were annotated to six cellular immunity pathways including endocytosis, lysosome, phagosome, ubiquitin mediated proteolysis, metabolism of xenobiotics by cytochrome P450, and insect hormone biosynthesis. Moreover, 284 (164) internal ribosome entry site (IRES) and 54 (26) ORFs were identified from DEcircRNAs in AcCK1 vs AcT1 (AcCK2 vs AcT2) comparison group; additionally, ORFs in DEcircRNAs in midgut at 7 dpi with microsporidian were associated with several cellular immune pathways including endocytosis and ubiquitin-mediated proteolysis. Ultimately, RT-qPCR results showed that the expression trends of six DEcircRNAs were consistent with those in transcriptome data. These results demonstrated that microsporidian altered the expression pattern of circRNAs in host, and DEcircRNAs were likely to regulate host cellular and humoral immune response to microsporidian infection. Our findings lay a foundation for clarifying the mechanism underlying host immune response to microsporidian infection and provide a new insight into interaction between Asian honey bee and microsporidian.